Cooccurrence of Darier’s Disease and Epilepsy: A Pediatric Case Report and Review of the Literature - Tamer Celik; Umit Celik; Cigdem Donmezer; Mustafa Komur; Orkun Tolunay; Pelin Demirtürk (Case Reports in Pediatrics)
Darier’s disease is a skin disorder characterized by multiple eruptions of hyperkeratosis or crusted papules at seborrheic areas with histologic acantholysis and dyskeratosis. It is caused by mutations in a single gene, being ATP2A2 and that is expressed in the skin and brain. The cooccurrence of various neurologic and psychiatric diseases with Darier's disease has been reported frequently in literature. They include mood disorders, epilepsy, encephalopathy, and schizophrenia. In this study, we report a pediatric case with the cooccurrence of Darier’s disease and epilepsy. We also revised current English literature on this topic.